1995
DOI: 10.1161/01.hyp.26.3.503
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Pulse Wave Analysis for the Early Detection of Vascular Disease

Abstract: A noninvasive technique has been developed and validated for calculating capacitive and oscillatory systemic arterial compliance with the use of pulse wave analysis and a modified Windkessel model. Application of the technique to subjects with hypertension, postmenopausal women with symptomatic coronary artery disease, and appropriate control subjects has confirmed a reduction of oscillatory compliance in the disease states and an increase in capacitive and oscillatory compliances in response to vasodilator dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
312
1
11

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 432 publications
(332 citation statements)
references
References 26 publications
7
312
1
11
Order By: Relevance
“…Furthermore, Cohn et al 39 found in postmenopausal women with documented atherosclerosis, compared with healthy postmenopausal controls, that the oscillatory but not the capacitive systemic arterial compliance was reduced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Cohn et al 39 found in postmenopausal women with documented atherosclerosis, compared with healthy postmenopausal controls, that the oscillatory but not the capacitive systemic arterial compliance was reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, the sample had been stratified by sex and age (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59), у60 years), in an attempt to recruit the same number of subjects in each stratum. Households were identified from population registries as persons who shared the same address.…”
Section: Study Populationmentioning
confidence: 99%
“…PWA was performed by a trained investigator using the standard technique (26). It was administered in the morning, after the subject had fasted overnight.…”
Section: Methodsmentioning
confidence: 99%
“…The modified Windkessel model is a mathematical depiction of the vasculature as a number of related components: capacitive compliance (C1 index), oscillatory or reflective compliance (C2 index), inductance, and resistance (systemic vascular resistance), measured during the diastolic decay portion of the cardiac cycle (25). This technique has been validated against invasive tests of arterial compliance (26), and reduced arterial compliance has been demonstrated in patients with hypertension, patients with diabetes, and smokers (27)(28)(29). Increased arterial stiffness as measured by pulse wave velocity has also been correlated with coronary atherosclerosis (30) and has been shown to predict coronary events and mortality in patients with hypertension (31,32).…”
mentioning
confidence: 99%
“…[4][5][6] During the recent years, technological progress has enabled reliable measurement of vascular compliance, a means of assessing the early stages of vascular disease. One such technique, arterial pulse-wave contour analysis, involves quantifying the amount of arterial stiffening and can be regarded as a valid marker of generalized atherosclerosis 7,8, as well as a predictor of cardiovascular mortality. [9][10][11] Estimation of vascular compliance may serve as a surrogate end point for morbid risk and treatment benefit.…”
Section: Introductionmentioning
confidence: 99%